2003
DOI: 10.1007/s00125-002-1025-0
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of undiagnosed diabetes mellitus in Southern Germany: Target populations for efficient screening. The KORA survey 2000

Abstract: About 40% of the population aged 55 to 74 years in the Augsburg region have disturbed glucose tolerance or diabetes. Half of the total cases with diabetes are undiagnosed. Cardiovascular risk factors worsen among glucose tolerance categories, indicating the need for screening and prevention. Screening for undiagnosed diabetes could be most efficient in individuals with abdominal adiposity (men), hypertriglyceridaemia (women), hypertension, and parental diabetes history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
345
3
72

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 507 publications
(448 citation statements)
references
References 24 publications
28
345
3
72
Order By: Relevance
“…Cooperative Health Research in the Region of Augsburg Survey 4 (KORA S4) study population has been described extensively (25)(26)(27)(28)(29). In the age range 55-74 years, 120 individuals with newly diagnosed type 2 diabetes (and thus without antidiabetic treatment, which could interfere with adiponectin and immune marker levels) and 242 subjects with impaired glucose tolerance (IGT) were available for analysis.…”
Section: Research Design and Methods -The Population-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperative Health Research in the Region of Augsburg Survey 4 (KORA S4) study population has been described extensively (25)(26)(27)(28)(29). In the age range 55-74 years, 120 individuals with newly diagnosed type 2 diabetes (and thus without antidiabetic treatment, which could interfere with adiponectin and immune marker levels) and 242 subjects with impaired glucose tolerance (IGT) were available for analysis.…”
Section: Research Design and Methods -The Population-basedmentioning
confidence: 99%
“…The measurement of anthropometric parameters, metabolic and immunological variables (from fasting blood samples), blood pressure, and the assessment of alcohol intake, smoking, and physical activity has been described previously (25)(26)(27)(28)(29). Hypertension was defined as use of antihypertensive treatment or systolic blood pressure Ն140 mmHg or diastolic blood pressure Ն90 mmHg.…”
Section: Research Design and Methods -The Population-basedmentioning
confidence: 99%
“…The study designs have been described in detail elsewhere 9,18,39 unrelated men and women between 25 and 74 years of age. All subjects had to complete a standardised questionnaire, that, in addition to demographic data included the basic allergy questions of the European Community Respiratory Health Survey (ECRHS) on respiratory health 40 .…”
Section: Study Populationsmentioning
confidence: 99%
“…The KORA Survey 2000, a population-based study on prevalence of diabetes and IGT in a 55-to 74-year-old population in Germany reported a total diabetes prevalence of about 17%; an additional 23% of the population had IGT or IFG. Half of the total cases with diabetes were previously undiagnosed [3]. Thus, the prevalence of abnormal glucose tolerance found in southern Germany is among the highest reported in European countries [4][5][6], emphasising the need for prevention.…”
Section: Introductionmentioning
confidence: 99%